INVESTING IN THE FUTURE: THE CRITICAL ROLE OF EARLY CHILDHOOD EDUCATION FOR FAMILIES, CHILDREN, AND SOCIETY - Monica TURTUREAN (International Journal of Social and Educational Innovation)
Investing in early childhood education is a key strategy for building a strong future for families, children, and society as a whole. This study aimed to explore the perceptions of 62 early childhood educators and 62 parents regarding the importance of early education in child development and societal advancement. Using a structured questionnaire, we collected qualitative and quantitative data to better understand stakeholders' views on how early education impacts children’s cognitive, emotional, and social skills, as well as its broader societal benefits. The findings revealed that both educators and parents recognize early childhood education as fundamental for fostering resilience, critical thinking, social responsibility, and future academic success. However, the study also identified a significant gap between the recognized importance of early education and the level of societal and familial investment in these programs.